Application of the Al-Wakalah Agreement in Buying and Selling in Sharia Banking - Aulia Rahmah (Takaza Innovatix Labs Ltd., 2025)
This study examines the application of the Al-Wakalah contract in sales transactions in Indonesian Islamic banking, amidst rapid digitalization and challenges of sharia compliance. The aim is to outline the implementation, identify compliance issues, and evaluate its potential to replace conventional contracts. Using a descriptive qualitative method through library research, the population includes post-2000 Al-Wakalah literature and fatwas, purposively sampling 25 Google Scholar sources (2013-2025). The instrument is a library guide, analyzed by the Miles and Huberman model with a focus on the pillars of wakalah. The results show that Al-Wakalah functions dually as a ujrah service (transfer, L/C) and a supporter of Murabahah, guaranteeing asset ownership according to DSN-MUI Fatwa No. 10/2000, but is vulnerable to gharar due to unclear documentation. In conclusion, strengthening SOPs is necessary for sharia integrity, with limited field data suggesting mixed-methods in further studies.